Perceptually Correlated Parameters of Musical Instrument Tones - BEAUCHAMP, James W. (Archives of Acoustics, 2011)
In Western music culture instruments have been developed according to unique instrument acoustical features based on types of excitation, resonance, and radiation. These include the woodwind, brass, bowed and plucked string, and percussion families of instruments. On the other hand, instrument performance depends on musical training, and music listening depends on perception of instrument output. Since musical signals are easier to understand in the frequency domain than the time domain, much effort has been made to perform spectral analysis and extract salient parameters, such as spectral centroids, in order to create simplified synthesis models for musical instrument sound synthesis. Moreover, perceptual tests have been made to determine the relative importance of various parameters, such as spectral centroid variation, spectral incoherence, and spectral irregularity. It turns out that the importance of particular parameters depends on both their strengths within musical sounds as well as the robustness of their effect on perception. Methods that the author and his colleagues have used to explore timbre perception are: 1) discrimination of parameter reduction or elimination; 2) dissimilarity judgments together with multidimensional scaling; 3) informal listening to sound morphing examples. This paper discusses ramifications of this work for sound synthesis and timbre transposition.